2004
DOI: 10.1073/pnas.0308232100
|View full text |Cite
|
Sign up to set email alerts
|

Specific mutations of hepatitis B virus in plasma predict liver cancer development

Abstract: A major risk factor for hepatocellular carcinoma (HCC) is hepatitis B virus (HBV), whose pathogenesis is exacerbated by the acquisition of mutations that accelerate carcinogenesis. We examined, with mass spectrometry, the temporality of an HBV 1762 T ͞1764 A double mutation in plasma and tumors. Initial studies found that 52 of 70 (74.3%) tumors from patients residing in Qidong, People's Republic of China, contained this HBV mutation. Paired plasma samples were available for six of the tumor specimens; four tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 46 publications
7
124
0
2
Order By: Relevance
“…Only a few studies have addressed the questions of the rate of HBV mutations in tumor tissues (Pontisso et al, 1984;Raimondo et al, 1988;Clementi et al, 1993). However, our group and others have shown that mutations in basal core promoter, PreC/C, envelope and X sequences can be identified in HCC tissues (Minami et al, 1996;Fan et al, 2000Fan et al, , 2001Tu et al, 2001;Oon et al, 2002;Iavarone et al, 2003;Kao et al, 2003;Kuang et al, 2004). We have observed that in the Core gene, most of the non-synonymous mutations (i.e.…”
Section: The Role Of Hepatitis B Virus In Liver Cell Carcinogenesismentioning
confidence: 79%
See 1 more Smart Citation
“…Only a few studies have addressed the questions of the rate of HBV mutations in tumor tissues (Pontisso et al, 1984;Raimondo et al, 1988;Clementi et al, 1993). However, our group and others have shown that mutations in basal core promoter, PreC/C, envelope and X sequences can be identified in HCC tissues (Minami et al, 1996;Fan et al, 2000Fan et al, , 2001Tu et al, 2001;Oon et al, 2002;Iavarone et al, 2003;Kao et al, 2003;Kuang et al, 2004). We have observed that in the Core gene, most of the non-synonymous mutations (i.e.…”
Section: The Role Of Hepatitis B Virus In Liver Cell Carcinogenesismentioning
confidence: 79%
“…HBx with mutations in amino acids 130 and 131 have been frequently reported and may be associated with the severity of chronic hepatitis; these mutations have also been detected in HCC (Yotsuyanagi et al, 2002;Iavarone et al, 2003;Leon et al, 2005), and a recent study of serum samples indicated that these mutations arise before the development of HCC (Kuang et al, 2004). However, the functional consequences of these mutated HBx proteins are still unclear.…”
Section: Hbv-related Hcc D Kremsdorf Et Almentioning
confidence: 99%
“…Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies. In fact, a prospective cohort of approximately 1,600 high-risk individuals in Qidong, China, showed that A1762T/G1764A mutations were detected in approximately 50% of HCC cases before cancer development, suggesting that these variants would indicate a high potential risk for hepatocarcinogenesis [22]. It has been reported that the development of A1762T/G1764A mutations is associated with HBV genotype and their prevalence is higher in genotype C than genotype B [8].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiological studies also support the hypothesis that mutant HBx integrated in HCC is positively associated with TP53 249 ser mutations. In both China and Thailand, analysis of plasma DNA revealed a frequent concordance between HBV 1762 T /1764 A and TP53 249 ser DNA in plasma at the time of HCC diagnosis (Kuang et al, 2004(Kuang et al, , 2005. The double mutant resides in the HBx open reading frame within HBV, and results in lysine to methionine and valine to isoleucine at HBx codons 130 and 131, respectively.…”
Section: Tp53 Mutations and Hcc Sp Hussain Et Almentioning
confidence: 99%